2019
DOI: 10.1090/tran/7584
|View full text |Cite
|
Sign up to set email alerts
|

Residue formulas for logarithmic foliations and applications

Abstract: We prove a residual formula in terms of the logarithmic indices for one-dimensional holomorphic foliations, with isolated singularities, and logarithmic along normally crossing divisors. As application we provide a formula for the number of singularities in the complement of the invariant divisor on projective spaces. We also give a formula for the total sum of the logarithmic indices if the the singular set of the foliation is contained in the invariant divisor. Finally, we obtain a a Poincaré-Hopf type formu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The section C 0 being in the support of ∆ means that F is regular at a general point p ∈ C 0 and the leaf that passes through p is transverse Consequently, a = m, b = (a + 1)e, ∆ = aC 0 and there exist s = b + 2 − 2g invariant fibers. This proves case (5). If F does not fit in any of the previous cases, then it has a singularity on a generically transverse fiber.…”
Section: µ(F P)mentioning
confidence: 53%
See 1 more Smart Citation
“…The section C 0 being in the support of ∆ means that F is regular at a general point p ∈ C 0 and the leaf that passes through p is transverse Consequently, a = m, b = (a + 1)e, ∆ = aC 0 and there exist s = b + 2 − 2g invariant fibers. This proves case (5). If F does not fit in any of the previous cases, then it has a singularity on a generically transverse fiber.…”
Section: µ(F P)mentioning
confidence: 53%
“…In [5] the authors proved more general results for an one-dimensional foliation F on a compact complex manifold X, of dimension n, with isolated singularities and an F -invariant hypersurface S. They proved under mild hypotheses on the singularities that lie on S that X c n (T X (− log S) ⊗ K F ) = p∈Sing(F )∩{X\S}…”
Section: Bounds For Foliations On Geometrically Ruled Surfacesmentioning
confidence: 99%
“…In the context of a hypersurface V invariant by a one-dimensional foliation F , we have the following Baum-Bott type theorem [34,33]: if F has isolated singularities and V is a normal crossing divisor, then…”
Section: Characteristic Classes and Residuesmentioning
confidence: 99%
“…He showed that the image sheaf of the logarithmic residues coincides with the sheaf of regular meromorphic differential forms introduced by D. Barlet [5] and M. Kersken [15,16]. We refer the reader to [4,8,9,10,12,29,30] for more recent results on logarithmic residues.…”
Section: Introductionmentioning
confidence: 97%